Synthesis and Characterization of Activated Carbon/Alginate-Cu Composites - Sari, Maya Novita; Muchtar, Zainuddin; Jasmidi, Jasmidi; Rahmah, Siti; Pulungan, Ahmad Shafwan; Zubir, Moondra; Selly, Rini; Faradilla, Putri (Indonesian Journal of Chemical Science and Technology (IJCST), 2023)
OPEFB is one source of natural fiber-based composites which have the potential to become activated carbon. This study aims to synthesize and characterize the activated carbon/alginate -Cu composite. The characterization used in this study is FTIR. The results of this study The synthesis of activated carbon/alginate -Cu composites began with a process of carbonization and activation with H3PO4 to produce Activated Carbon. Alginate using commercial alginate. Furthermore, the three ingredients were mixed until homogeneous and put into a 0.1M CuSO4 solution to produce beads. The characterization of FTIR characterization on the activated carbon/alginate-Cu composite contained the functional group OH group, triple C bond from stretching alkyne, C=C aromatic group, C-H alkane group, C-O group , the P=O stretching vibration of the P-O-C group and the alcohol OH group expressing the active carbon; there are functional groups of hydroxyl (OH), carboxyl, carbonyl, and C-O-C and “COOH bonds which represent alginate and there are OH functional groups, stretching C-H bonds, C-O stretching, stretching C-C. The KALg Cu13 sample had a peak at a wavelength of 2838.79 Cm-1 Where the four samples show the presence of Câ‰¡N groups